Asian development outlook 2018 supplement the outlook firms as trade conflict pauses. (Asian Development Outlook Series., 2018)
Backed by robust domestic demand, developing Asia continues to weather external headwinds.Despite challenges brought about by trade conflict, growth forecasts for developing Asia remain unchanged at 6.0% for 2018 and 5.8% for 2019, as envisaged in September in Asian Development Outlook (ADO) 2018 Update. East Asia and the Pacific are on track to meet growth projections. Unexpectedly strong expansion in Central Asia offsets small downward revisions for South and Southeast Asia in 2019. Excluding the newly industrialized economies of Hong Kong, China; the Republic of Korea; Singapore; and Taipei,China, the regional growth outlook is maintained at 6.5% for 2018 and 6.3% for 2019. The collective growth projections for the major industrial economies of the United States (US), the euro area, and Japan are retained from the Update. Favorable outcomes in the US and the euro area confirm that the major industrial economies will realize growth forecasts in the Update at 2.3% for 2018 and 2.1% for 2019, though an unexpected contraction in Japan in the third quarter warrants a slight downgrade to its 2018 growth projection.